Quench dynamics of a weakly interacting disordered Bose gas in momentum space - Thibault Scoquart; Thomas Wellens; Dominique Delande; Nicolas Cherroret (Physical Review Research, 2020)
We study theoretically the out-of-equilibrium dynamics in momentum space of a weakly interacting disordered Bose gas launched with a finite velocity. In the absence of interactions, coherent multiple scattering gives rise to a background of diffusive particles, on top of which a coherent backscattering interference emerges. We revisit this scenario in the presence of interactions, using a diagrammatic quantum transport theory. We find that the dynamics is governed by coupled kinetic equations describing the thermalization of the diffusive and coherent components of the gas. This phenomenon leads to a destruction of coherent backscattering, well described by an exponential relaxation whose rate is controlled by the particle collision time. These predictions are confirmed by numerical simulations.